Revealing the Role of Streamer Traits on Perceived Value and Impulsive Buying Behavior in TikTok Live Shopping - Muhammad Gaizka Darmawangsa; Afrima Widanti (Universitas Negeri Semarang, 2026)
This study research investigates the phenomenon of low purchase conversion rates amid the rapid growth of e-commerce and the widespread adoption of TikTok Live Shopping features in Indonesia. The study conceptualizes five streamer characteristics, namely attractiveness, popularity, experience, information quality, and interactivity, as stimuli; perceived value as the organism; and impulsive buying behavior as the consumer response. This research employs a quantitative approach using primary data collected through an online questionnaire administered to 225 valid respondents who had previously made purchases through Mami Louisse’s TikTok live shopping sessions. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that all five characteristics have a positive and significant effect on the formation of perceived value. Specifically, information quality emerges as the strongest determinant influencing consumers’ perceived value, surpassing both popularity and physical attractiveness. Furthermore, the study confirms that perceived value acts as the primary predictor driving impulsive buying behavior, with a large effect size. These findings imply that within the live shopping ecosystem, substantive elements, particularly the accuracy of product information, are more crucial than mere visual entertainment in triggering spontaneous purchase decisions.